Duganella lactea sp. nov., Duganella guangzhouensis sp. nov., Duganella flavida sp. nov. and Massilia rivuli sp. nov., isolated from a subtropical stream in PR China and proposal to reclassify Duganella ginsengisoli as Massilia ginsengisoli comb. nov. Issue 8 (24th August 2020) - Lu, Huibin; Deng, Tongchu; Liu, Feifei; Wang, Yonghong; Yang, Xunan; Xu, Meiying
Abstract : Five Gram-stain-negative, catalase- and oxidase-positive, rod-shaped and motile strains (FT50W T, FT80W T, FT92W T, FT94W and FT135W T ) were isolated from a subtropical stream in PR China. Comparisons based on 16S rRNA gene sequences showed that strains FT50W T, FT94W and FT135W T take strain Duganella sacchari Sac-22 T, and strains FT80W T and FT92W T take strain Duganella ginsengisoli DCY83 T as their closest neighbour in the phylogenetic trees, respectively. The G+C contents of strains FT50W T, FT80W T, FT92W T, FT94W and FT135W T were 63.3, 62.4, 62.8, 63.8 and 60.8 %, respectively. The reconstructed phylogenomic tree based on concatenated 92 core genes showed that strains FT50W T, FT80W T, FT94W and FT135W T clustered together with species of the genus Duganella, but strains FT92W T and D. ginsengisoli KCTC 42409 T were located in the clades of the genus Massilia . The calculated pairwise average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) values among strains FT50W T, FT80W T, FT92W T, FT94W, FT135W T and related strains were in the ranges of 75.6–87.8% and 20.3–33.8% except that the values between strains FT50W T and FT94W were 98.7 and 89.2%, respectively. The respiratory quinone of these five strains was Q-8. The major fatty acids were C16 : 1 ω 7 c, C16 : 0, C18 : 1 ω7 c and C12 : 0 . The polar lipids included phosphatidylethanolamine, phosphatidylglycerol and one unidentified phospholipid. Considering the distinct phylogenetic relationships of D. ginsengisoli with species of the genus Massilia in the phylogenomic tree, it was reasonable to transfer D. ginsengisoli to the genus Massilia as Massilia ginsengisoli comb. nov. Combining the results of phylogenomic analysis, ANI and dDDH data, and a range of physiological and biochemical characteristics together, strains FT50W T and FT94W should belong to the same species and be assigned to genus Duganella with strains FT80W T and FT135W T together, and strain FT92W T should be assigned to the genus Massilia, for which the names Duganella lactea sp. nov. (type strain FT50W T =GDMCC 1.1674 T =KACC 21466 T ), Duganella guangzhouensis sp. nov. (FT80W T =GDMCC 1.1678 T =KACC 21470 T ), Duganella flavida sp. nov. (FT135W T =GDMCC 1.1745 T =KACC 21659 T ) and Massilia rivuli sp. nov. (FT92W T =GDMCC 1.1682 T =KACC 21474 T ) are proposed.